Mixed Finite Element Formulation for Navier–Stokes Equations for Magnetic Effects on Biomagnetic Fluid in a Rectangular Channel - Erwan Hafizi, Kasiman; Ahmad Kueh, Beng Hong; Airil Yasreen, Mohd Yassin; Norsarahaida, Saidina Amin; Mugahed, Amran; Roman, Fediuk; Evgenii Vladimirovich, Kotov; Gunasekaran, Murali (MDPI, 2022)
: The article presents the mixed finite element formulation for examining the biomagnetic fluid dynamics as governed by the Navier–Stokes equation, coupled with energy and magnetic expressions. Both ferrohydrodynamics and agnetohydrodynamics describe the additional magnetic effects. For model discretization, the Galerkin weighted residual method was performed. Departing from a good agreement with existing findings, a biomagnetic flow (blood) in a straight rectangular conduit was then simulated in the presence of a spatially changing magnetic distribution. By virtue of negligible spatial variation influence from the magnetic field, the effects of Lorentz force were not presently considered. It was further found that the model accurately exhibits the formation and distribution of vortices, temperature, and skin friction located adjacent to and remotely from the source of magnetic load following a rise in the magnetic intensity.